2009
DOI: 10.1002/mrm.21937
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of gadolinium‐based MR contrast agents with choline: Implications for MR spectroscopy (MRS) of the breast

Abstract: It has been shown that magnetic resonance spectroscopy (MRS) can improve the specificity of the MR examination by the spectroscopic detection of choline (Cho). Commonly, the lesion is first visualized on postcontrast studies, and the MRS voxel is prescribed accordingly. The implicit assumption made in this approach is that the presence of gadolinium-based contrast agents will have a negligible effect on the MR spectra obtained from the lesion. In this work, we examined this assumption by determining the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…It has previously been shown that negatively charged chelates (such as Magnevist) may lead to an underestimation of tCho levels [28]. The tCho detection was higher in patients examined after administration of Magnevist as contrast agent (86%) compared to Omniscan (55%).…”
Section: Discussionmentioning
confidence: 97%
“…It has previously been shown that negatively charged chelates (such as Magnevist) may lead to an underestimation of tCho levels [28]. The tCho detection was higher in patients examined after administration of Magnevist as contrast agent (86%) compared to Omniscan (55%).…”
Section: Discussionmentioning
confidence: 97%
“…Of note, a trend for a higher sensitivity of 1H-MRS was observed when acquisition is performed before contrast injection, due to a detrimental effect of ionic-charged contrast materials in both experimental and clinical settings (38). As lesion localization (the placement of the spectroscopic volume of interest) has to be made on CE images (especially for otherwise not visible small lesions), the majority of 1H-MRS studies were performed after contrast injection, potentially implying a suboptimal sensitivity.…”
Section: Diagnostic Performance Of 1h-mrsmentioning
confidence: 99%
“…In addition, contrast-enhanced sequences can be used to directly position the voxel of interest over well-vascularized and viable areas of tumor [21]. Findings by Lenkinski et al [22] are evidence of exclusive use of neutral chelates of gadolinium in choline MRS to avoid underestimation of the choline peak if MRS is performed after contrast administration.…”
Section: Proton (1h) Mr Spectroscopic Techniquementioning
confidence: 99%